2012
DOI: 10.1186/1477-9560-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Cold autoimmune haemolytic anaemia secondary to Epstein Barr virus infection presenting with peripheral gangrene; case report

Abstract: A sixty year old male presented with dark urine, symptomatic anaemia and peripheral gangrene following cold exposure. Investigations revealed that he had haemolysis and serological evidence of recent Epstein Barr virus infection. Although acrocyanosis is commonly associated with cold agglutinin disease, gangrene is a rare complication. Management of secondary cold agglutinin disease is mainly supportive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Polyclonal antibodies, typically seen in the postinfectious setting, are selfresolving, although treatment of the underlying infection may hasten resolution. Postinfectious cold agglutinins are seen with viral and bacterial pathogens, including mycoplasma, 19 Epstein-Barr virus, [20][21][22] and legionella. Case reports of cold agglutinin hemolysis induced by varicella, [23][24][25] Citrobacter, 26 and influenza 27,28 have been described.…”
Section: History and Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyclonal antibodies, typically seen in the postinfectious setting, are selfresolving, although treatment of the underlying infection may hasten resolution. Postinfectious cold agglutinins are seen with viral and bacterial pathogens, including mycoplasma, 19 Epstein-Barr virus, [20][21][22] and legionella. Case reports of cold agglutinin hemolysis induced by varicella, [23][24][25] Citrobacter, 26 and influenza 27,28 have been described.…”
Section: History and Mechanismmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45] In addition to hemolysis, clinical manifestations include coldinduced circulatory symptoms; livedo reticularis, Raynaud disease, acrocyanosis and, rarely, cutaneous necrosis. 20,[46][47][48][49] Berentsen et al 5 reported cold-induced symptoms in more than 90% of patients. Splenomegaly is not prominent in CAD.…”
mentioning
confidence: 99%
“…[3][4][5] Several reports of EBV infections associated with cold agglutinins have been described; [6][7][8][9][10][11] all were associated with IgM. Anti-I and anti-i are more common cold-agglutinin specific antibodies directed against poly-N-acetyl-lactosamine type 2 sequences.…”
mentioning
confidence: 99%
“…The haemolysis is due to complement fixation in the intravascular compartment, and the majority of the complement coated cells are destroyed extravascularly by the reticulo-endothelial system. 2 Cold agglutinin disease was first reported in animals in 1903 by Landsteiner, and first human case reported in 1918 by Clough. 3 It is a rare disease, most often affecting females in the seventh decade of life, with an incidence of one case per million people per year.…”
Section: Discussionmentioning
confidence: 99%